Survivorship Care Effects on Gynecological and Breast Cancer Survivors: A Systematic Review and Meta-Analysis - Lina Anisa Nasution; Lisna Anisa Fitriana; Irma Darmawati; Andria Pragholapati; Dhika Dharmansyah; Usa Sunairattanaporn (JURNAL INFO KESEHATAN, 2026)
Survivorship care aims to address the long-term physical and psychosocial needs of cancer survivors, yet evidence regarding its effectiveness and optimal components remains inconsistent. This study aimed to evaluate the effectiveness of survivorship care interventions on quality of life and related outcomes among gynecological and breast cancer survivors and explored intervention components associated with improved outcomes with PRISMA guidelines. Seven databases were searched for English-language studies involving adult gynecological and/or breast cancer survivors who had completed primary treatment and received survivorship care interventions compared with usual care. A random-effects model was used to estimate pooled effects. Heterogeneity was assessed using the I² statistic, and subgroup analyses and meta-regression were performed. Risk of bias was evaluated using the Cochrane Risk of Bias tool. The review was registered in PROSPERO (CRD42023402234). Eight randomized controlled trials comprising 1,464 participants were included. Survivorship care interventions significantly improved overall quality of life (SMD = 0.26; 95% CI: 0.08–0.44), physical well-being (SMD = 0.26; 95% CI: 0.12–0.41), mental well-being (SMD = 0.17; 95% CI: 0.03–0.31), and reduced depressive symptoms (SMD = 0.20; 95% CI: 0.00–0.41), with low to moderate heterogeneity across outcomes. Subgroup analyses indicated that multimodal interventions incorporating lectures, discussions, consultations, and online coaching particularly those supported by mobile health applications were associated with greater benefits, especially in physical well-being. Several studies demonstrated moderate risk of bias, mainly related to randomization and reporting. Survivorship care interventions provide small to moderate clinically meaningful improvements in quality of life and psychosocial outcomes among gynecological and breast cancer survivors. These findings support the integration of structured, multidisciplinary, and technology assisted survivorship care into routine oncology practice, while highlighting the need for higher quality, context sensitive trials.